Hemothorax after sneezing - Andrew Neff; Cassandra Bradby (Journal of the American College of Emergency Physicians Open, 2023)
Abstract Acute hemothorax is generally known to be a sequela of trauma to the chest, rupture of aortic aneurysm, or aortic dissection. Other causes of hemothorax have been attributed to iatrogenic, vascular, neoplastic, coagulopathy, or infectious processes. Although there has been a single report of spontaneous rupture of intercostal artery after coughing, there have been no reports of the same from sneezing. This rare presentation highlights the importance of a full evaluation for patients who present with viral symptoms such as sneezing or coughing along with a complaint of chest pain because massive hemothorax can be life‐threatening.